A Singapore Founding Father: An Appreciation of S Rajaratnam - Ng, Joshua (2016)
S Rajaratnam’s contributions in various fields, like those of other founding fathers, have allowed his successors to build upon a robust legacy. Going forward, his clarity of ideas, principles and purpose will be a guide post for Singaporeans to problem-solve and to manage change and challenges.